Basic Sulfate Precipitation of Zirconium from Sulfuric Acid Leach Solution - Yiqian Ma; Srecko Stopic; Xuewen Wang; Kerstin Forsberg; Bernd Friedrich (Metals, 2020)
H2SO4 was ensured to be the best candidate for Zr leaching from the eudialyte. The resulting sulfuric leach solution consisted of Zr(IV), Nb(V), Hf(IV), Al(III), and Fe(III). It was found that ordinary metal hydroxide precipitation was not feasible for obtaining a relatively pure product due to the co-precipitation of Al(III) and Fe(III). In this reported study, a basic zirconium sulfate precipitation method was investigated to recover Zr from a sulfuric acid leach solution of a eudialyte residue after rare earth elements extraction. Nb precipitated preferentially by adjusting the pH of the solution to around 1.0. After partial removal of SO42− by adding 120 g of CaCl2 per 1L solution, a basic zirconium sulfate precipitate was obtained by adjusting the pH to ~1.6 and maintaining the solution at 75 °C for 60 min. Under the optimum conditions, the loss of Zr during the SO42− removal step was only 0.11%, and the yield in the basic zirconium sulfate precipitation step was 96.18%. The precipitate contained 33.77% Zr and 0.59% Hf with low concentrations of Fe and Al. It was found that a high-quality product of ZrO2 could be obtained from the basic sulfate precipitate.